A phytic acid double cross-linked protein / carboxymethyl cellulose composite film and a preparation method and application thereof

CN122941184APending Publication Date: 2026-10-20SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610751348.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,尽管大豆分离蛋白具备上述成膜潜力,其工业化应用仍受到显著制约

Benefits of technology

(1)本发明将植酸引入大豆分离蛋白/羧甲基纤维素共混体系,利用植酸分子丰富的磷酸根基团与蛋白质氨基及多糖羟基形成多重交联位点,在大豆分离蛋白与羧甲基纤维素之间构建双交联网络,有效解决了纯大豆分离蛋白薄膜机械强度低、脆性大及耐水性差的本征缺陷,同时进一步提升了复合膜的致密性与热稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a phytic acid-crosslinked protein / carboxymethyl cellulose composite membrane, its preparation method, and its applications, belonging to the field of edible hydrophobic composite membrane preparation technology. The preparation method includes: dispersing soy protein isolate in deionized water, heating and adjusting the pH to 10, adding glycerol and gelatin and mixing, adjusting the temperature, then adding carboxymethyl cellulose and mixing evenly, subsequently adjusting the pH to 7, adding phytic acid to obtain a film-forming solution, and drying the film-forming solution to obtain the phytic acid-crosslinked soy protein isolate / carboxymethyl cellulose composite membrane. This invention utilizes phytic acid to construct a double crosslinking network between soy protein isolate and carboxymethyl cellulose, effectively solving the problems of poor mechanical properties, high brittleness, and insufficient hydrophobicity of soy protein isolate membranes, while significantly improving the thermal stability of the composite membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of edible hydrophobic composite membrane preparation technology, specifically relating to a phytic acid double crosslinked protein / carboxymethyl cellulose composite membrane, its preparation method, and its application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Traditional plastics, with their lightweight, durability, low cost, and excellent barrier properties, have long been deeply integrated into all aspects of modern production and life. However, with the rapid expansion of their use, the difficulty in natural disposal after waste is creating a serious ecological crisis. Faced with this dilemma, the development of environmentally friendly packaging materials with biodegradable properties is rapidly becoming a collaborative effort between academia and industry. The core challenge lies in enabling these new materials to retain the key properties of traditional plastics. In this context, biodegradable films based on natural polymers exhibit considerable application potential due to their wide availability of raw materials, strong renewability, good biocompatibility, and low environmental impact.

[0004] Among biodegradable packaging materials, plant proteins are highly valued due to their abundant sources, renewability, and good film-forming properties, and their performance can be regulated by combining them with components such as polysaccharides. During thermal denaturation, soy protein isolate exposes its internal hydrophobic groups and thiol groups, which are oxidized to form intermolecular disulfide bonds, driving protein chain cross-linking and constructing a three-dimensional network. However, despite its film-forming potential, the industrial application of soy protein isolate is significantly limited. The inherent defects of pure soy protein isolate films lie in their fragility in hydrated environments, specifically manifested as insufficient mechanical strength, poor water resistance, and low thermal stability. These defects stem from the presence of numerous hydrophilic amino acid residues in the protein chains, making the films prone to swelling and even structural collapse under high humidity conditions. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a phytic acid double crosslinked protein / carboxymethyl cellulose composite membrane, its preparation method, and its application, which can improve the film-forming properties of proteins.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a phytic acid double crosslinked protein / carboxymethyl cellulose composite membrane, the raw materials of which include phytic acid, protein and carboxymethyl cellulose; Proteins and carboxymethyl cellulose form physical cross-linking points through strong intermolecular hydrogen bonds; negatively charged phytic acid forms electrostatic salt bonds with cationic groups in proteins; and the phosphate groups of phytic acid and carboxyl groups on the carboxymethyl cellulose molecular chain construct a multiple hydrogen bond-coordination cross-linking network.

[0007] Secondly, the present invention provides a method for preparing the above-mentioned phytic acid double crosslinked protein / carboxymethyl cellulose composite membrane, comprising the following steps: Dissolve the protein in water, heat and adjust the pH to alkaline, add glycerol and gelatin and continue heating to react, adjust the temperature and then add carboxymethyl cellulose and mix well. Then adjust the pH to neutral, add phytic acid to obtain the film-forming solution, and dry the film-forming solution to obtain the final product.

[0008] Thirdly, the present invention provides the application of the above-mentioned phytic acid double crosslinked protein / carboxymethyl cellulose composite film or the phytic acid double crosslinked protein / carboxymethyl cellulose composite film prepared by the above preparation method in the packaging field.

[0009] Fourthly, the present invention provides a packaging material comprising the above-mentioned phytic acid double crosslinked protein / carboxymethyl cellulose composite film or the phytic acid double crosslinked protein / carboxymethyl cellulose composite film prepared by the above-mentioned preparation method.

[0010] One or more of the above technical solutions have the following advantages or beneficial effects: (1) This invention introduces phytic acid into the soybean protein isolate / carboxymethyl cellulose blend system. By utilizing the abundant phosphate groups of phytic acid molecules to form multiple cross-linking sites with the amino groups of proteins and the hydroxyl groups of polysaccharides, a double cross-linking network is constructed between soybean protein isolate and carboxymethyl cellulose. This effectively solves the inherent defects of pure soybean protein isolate film, such as low mechanical strength, high brittleness and poor water resistance. At the same time, it further improves the density and thermal stability of the composite film.

[0011] (2) This invention uses renewable soy protein isolate as the main raw material and prepares a biodegradable composite film with excellent comprehensive performance through a phytic acid double crosslinking strategy. This not only broadens the application value of soy protein in the field of green packaging, but also provides a new technical approach for the structural design of biodegradable composite films, which is conducive to promoting the development of the biodegradable packaging materials industry. Attached Figure Description

[0012] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0013] Figure 1FTIR curves of soy protein isolate films with different components prepared in Example 6; where a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 2 XRD curves of soy protein isolate films with different components prepared in Example 6; where a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 3 The DSC curves of soy protein isolate films with different components prepared in Example 6 are shown; where a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 4 Thermogravimetric curves of soy protein isolate films with different components prepared in Example 6 are shown; where a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 5 The images show the morphology of soy protein isolate films with different components prepared in Example 6. a1, b1, c1, d1, and e1 represent the surface morphology of pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively, magnified 500 times. a2, b2, c2, d2, and e2 represent the cross-sectional views of the pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 6The water contact angles of the soy protein isolate films with different components prepared in Example 6 are shown; where a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Figure 7 The tensile properties of soy protein isolate films with different components prepared in Example 6 are shown; wherein a, b, c, d, and e represent pure soy protein isolate film, soy protein isolate-carboxymethyl cellulose film, soy protein isolate-0.2 carboxymethyl cellulose-phytic acid film, soy protein isolate-0.5 carboxymethyl cellulose-phytic acid film, and soy protein isolate-0.8 carboxymethyl cellulose-phytic acid film, respectively. Detailed Implementation

[0014] Explanation of ae in the diagram: In Example 6, the membrane prepared by omitting steps (4) and (5) is denoted as a, which means that the carboxymethyl cellulose and phytic acid are omitted, and a pure soy protein isolate film is formed by adding soy protein isolate, glycerol and gelatin components.

[0015] In Example 6, step (5) was omitted and the membrane prepared with carboxymethyl cellulose accounting for 10 wt.% of soy protein isolate was designated as b. That is, phytic acid was omitted and soy protein isolate-carboxymethyl cellulose film was formed by adding carboxymethyl cellulose, soy protein isolate, glycerol and gelatin components.

[0016] In Example 6, the membrane prepared with carboxymethyl cellulose accounting for 4 wt.% of soybean protein isolate was denoted as c, which is soybean protein isolate-0.2 carboxymethyl cellulose-phytic acid membrane.

[0017] In Example 6, the membrane prepared with carboxymethyl cellulose accounting for 10 wt.% of soybean protein isolate was denoted as d, which is soybean protein isolate-0.5 carboxymethyl cellulose-phytic acid membrane.

[0018] In Example 6, the membrane prepared with carboxymethyl cellulose accounting for 16 wt.% of soybean protein isolate was denoted as e, which is soybean protein isolate-0.8 carboxymethyl cellulose-phytic acid membrane.

[0019] The inherent defects of the soy protein isolate film in this invention, such as high brittleness and poor water resistance, limit its practical application. Simply physical blending it with carboxymethyl cellulose is insufficient to block the water molecule permeation pathway at the molecular scale, resulting in limited improvement in barrier performance. This invention proposes a phytic acid double crosslinked soy protein isolate / carboxymethyl cellulose composite film, its preparation method, and its application.

[0020] This invention utilizes carboxymethyl cellulose (CMC) to improve the brittleness of films. Its mechanism lies in the abundance of carboxymethyl and hydroxyl groups on the CMC molecular chain, while soy protein isolate is rich in amide residues such as glutamine and asparagine, as well as exposed serine and threonine hydroxyl groups. During blending, the two form physical cross-linking points through strong intermolecular hydrogen bonds, promoting molecular-level interpenetration between soy protein isolate and CMC at the microscale. This significantly improves the film's density and cohesive energy density, thereby enhancing its mechanical strength. While the non-covalent interaction between soy protein isolate and CMC improves network uniformity, it cannot fundamentally block the permeation pathway of water molecules. This is because both components contain a large number of hydrophilic groups such as hydroxyl and carboxyl groups, which can still serve as effective binding sites for water molecules, resulting in consistently poor water-blocking performance of the composite film.

[0021] This invention introduces a phytic acid-based dual crosslinking strategy. Phytic acid, with its six phosphate groups in its molecular structure, is a highly efficient and non-toxic crosslinking agent. Under acidic conditions, negatively charged phytic acid forms strong electrostatic salt bonds with the cationic groups of lysine, histidine, and arginine residues in proteins. In addition to interacting with proteins, the phosphate groups of phytic acid can also form a multiple hydrogen bond-coordination crosslinking network with the carboxyl groups on the carboxymethyl cellulose molecular chain. This hierarchical dual crosslinking structure, which simultaneously anchors protein chains and locks polysaccharide chains, is expected to synergistically eliminate microphase separation voids within the film and significantly restrict the mobility of hydrophilic segments, thereby improving the structural compactness and hydrophobicity of the film at the molecular scale.

[0022] In one embodiment, the present invention provides a phytic acid double crosslinked protein / carboxymethyl cellulose composite membrane, the raw materials of which include phytic acid, soy protein isolate and carboxymethyl cellulose; Soy protein isolate and carboxymethyl cellulose form physical cross-linking points through strong intermolecular hydrogen bonds, enabling molecular-level interpenetration between soy protein isolate and carboxymethyl cellulose at the microscale. Negatively charged phytic acid forms electrostatic salt bonds with cationic groups in proteins; the phosphate groups of phytic acid form a multiple hydrogen bond-coordination cross-linking network with the carboxyl groups on the carboxymethyl cellulose molecular chain.

[0023] The protein includes soy protein isolate.

[0024] This invention introduces phytic acid into a soy protein isolate / carboxymethyl cellulose blend system. By utilizing the abundant phosphate groups of phytic acid molecules to form multiple cross-linking sites with the amino groups of proteins and the hydroxyl groups of polysaccharides, a double cross-linking network is constructed between soy protein isolate and carboxymethyl cellulose. This effectively solves the inherent defects of pure soy protein isolate films, such as low mechanical strength, high brittleness, and poor water resistance, while further improving the density and thermal stability of the composite film.

[0025] The selection of acids revealed that monocarboxylic acids (acetic acid) only promote protein chain unfolding by adjusting pH, but lack multidentate binding sites and cannot form an effective cross-linking network; polycarboxylic acids (citric acid) can form cross-links through esterification, but the cross-linking type is singular and the distribution of cross-linking points is difficult to control, resulting in a significant increase in film brittleness; high molecular weight acidic polysaccharides (hyaluronic acid) have large molecular weight and poor compatibility with carboxymethyl cellulose, and their introduction actually disrupts the uniformity of the soy protein isolate / carboxymethyl cellulose blend network.

[0026] In modifying the soybean protein of this invention, the chelating effect of phytic acid was used to enhance the cross-linking between soybean protein membrane molecules, thereby improving its performance. Phytic acid is an organophosphate compound with good biocompatibility extracted from plant seeds and has a high chelating capacity. The fundamental difference between phytic acid and the other three acids lies in its unique molecular structure—six phosphate groups symmetrically distributed on a six-carbon inositol ring backbone. This structure endows phytic acid with the following irreplaceable advantages: a dual-mechanism synergistic cross-linking ability. After partial deprotonation near pH=7, the phosphate groups carry a strong negative charge, which can form strong electrostatic salt bridges with the cationic groups of the lysine, arginine, and histidine residue side chains in soybean protein isolate; at the same time, the P=O and P-OH on the phosphate groups can act as hydrogen bond acceptors and donors, forming a wide range of multiple hydrogen bond networks with the carboxyl / hydroxyl groups on the CMC chain. This bidirectional cross-linking ability of "anchoring protein with one hand and grasping polysaccharide with the other" is completely absent in acetic acid, citric acid, and hyaluronic acid. This invention uses phytic acid as a cross-linking agent, and the resulting composite membrane has achieved significant improvements in mechanical properties and hydrophobic properties. The six phosphate groups provide abundant binding sites, enabling multi-site binding at the single-molecule level to form a dense and uniform cross-linked network. Electrostatic salt bridges and hydrogen bonds are non-covalent physical cross-links, which can further enhance the network strength of soybean protein.

[0027] In one embodiment, the present invention provides a method for preparing the above-mentioned phytic acid double-crosslinked protein / carboxymethyl cellulose composite membrane, comprising the following steps: Dissolve the protein in water, heat and adjust the pH to alkaline, add glycerol and gelatin and continue heating to react, adjust the temperature and then add carboxymethyl cellulose and mix well. Then adjust the pH to neutral, add phytic acid to obtain the film-forming solution, and dry the film-forming solution to obtain the final product.

[0028] Preferably, the preparation method includes: dispersing soy protein isolate in deionized water, heating and adjusting the pH to 10, adding glycerol and gelatin and mixing, adjusting the temperature, adding carboxymethyl cellulose and mixing evenly, then adjusting the pH to 7, adding phytic acid to obtain a film-forming solution, and drying the film-forming solution to obtain a phytic acid double crosslinked soy protein isolate / carboxymethyl cellulose composite membrane.

[0029] In some embodiments of this implementation, the solid-liquid ratio of protein to deionized water is 1:10~30 g / mL, specifically 1:10 g / mL, 1:12 g / mL, 1:15 g / mL, 1:18 g / mL, 1:19 g / mL, 1:19.5 g / mL, 1:19.6 g / mL, 1:19.7 g / mL, 1:19.8 g / mL, 1:19.9 g / mL, 1:20 g / mL, 1:20.1 g / mL, 1:20.2 g / mL, 1:20.2 g / mL, 1:20.4 g / mL, 1:20.5 g / mL, 1:20.8 g / mL, 1:21 g / mL, 1:21.5 g / mL, 1:22 g / mL, 1:25 g / mL, etc. 28 g / mL, 1:30 g / mL, etc., are preferred, with 1:15~25 g / mL being the ideal ratio. Experiments have shown that the solid-liquid ratio of protein to deionized water affects the membrane strength; at this ratio, the membrane strength is better. When the solid-liquid ratio of protein to deionized water is 1:19.6~20.4 g / mL, the membrane strength is even higher.

[0030] In some embodiments of this implementation, glycerol is 30-50 wt.% of the protein mass, specifically 30 wt.%, 32 wt.%, 35 wt.%, 38 wt.%, 39 wt.%, 39.5 wt.%, 39.6 wt.%, 39.8 wt.%, 40 wt.%, 40.1 wt.%, 40.2 wt.%, 40.4 wt.%, 40.5 wt.%, 41 wt.%, 42 wt.%, 45 wt.%, 48 wt.%, 50 wt.%, etc., preferably 35-45 wt.%. Experiments have shown that the amount of glycerol added affects the membrane strength; at this concentration, the membrane strength is better. When the glycerol content is 39.6-40.4 wt.% of the protein mass, the membrane strength is even higher.

[0031] In some embodiments of this implementation, the mass fraction of gelatin as protein is 10-30 wt.%, specifically 10 wt.%, 12 wt.%, 15 wt.%, 18 wt.%, 19 wt.%, 19.5 wt.%, 19.6 wt.%, 19.8 wt.%, 20 wt.%, 20.2 wt.%, 20.4 wt.%, 20.5 wt.%, 21 wt.%, 22 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, etc., preferably 15-25 wt.%. Experiments have shown that the amount of gelatin added affects the membrane strength; at this concentration, the membrane strength is better. When the volume fraction of gelatin as protein is 19.6-20.4 wt.%, the membrane strength is even higher.

[0032] In some embodiments of this implementation, the mass fraction of carboxymethyl cellulose as protein is 4-16 wt.%, specifically 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 9.5 wt.%, 9.6 wt.%, 9.9 wt.%, 10 wt.%, 10.1 wt.%, 10.5 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, etc., preferably 8-12 wt.%. Experiments have shown that the amount of carboxymethyl cellulose added affects various membrane properties, such as strength, brittleness, and hydrophobicity. When the mass fraction of carboxymethyl cellulose as protein is 9.9-10.1 wt.%, the membrane exhibits better strength, brittleness, and hydrophobicity.

[0033] In some embodiments of this implementation, the heating temperature of the protein and water reaction is 70-90°C, specifically 70°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, etc., preferably 76-84°C. The heating reaction time of the protein and water is 20-40 minutes. Furthermore, the pH of the protein aqueous solution is adjusted to alkaline, specifically 8-10, preferably 9-10.

[0034] The reaction temperature when adding glycerin and gelatin is 70~90℃, and the reaction time is 20~40min.

[0035] Temperature control is one of the key steps in the preparation process of this invention. The main components of soy protein isolate (7S and 11S globulins) require temperatures above 80°C to fully denature and unfold, exposing their internal active amino acid residues and providing reaction sites for the electrostatic anchoring of phytic acid. If the temperature is too low (<60°C), the protein fold structure does not open, the phosphate groups of phytic acid cannot form effective electrostatic salt bridges with soy protein isolate, and the double cross-linked network cannot be established. If the temperature is too high (>90°C), irreversible excessive aggregation of soy protein isolate occurs, and carboxymethyl cellulose undergoes thermal degradation. Therefore, 80°C is the only feasible temperature range for achieving a "complete double cross-linked network."

[0036] During the experiment, it was found that if the mixing and crosslinking of soy protein isolate, carboxymethyl cellulose, and phytic acid were carried out at room temperature (25°C), the mechanical strength and hydrophobic properties of the resulting film were significantly lower than those prepared at 80°C. This is because the globular protein structure of soy protein isolate at room temperature does not undergo sufficient thermal denaturation and expansion, and its internal cationic amino acid residues (such as lysine, arginine, and histidine) cannot be fully exposed. Consequently, phytic acid can only form partial hydrogen bonds with carboxymethyl cellulose, but cannot form effective electrostatic salt bridges with soy protein isolate, thus failing to truly achieve the "double crosslinking" effect described in this invention. Therefore, this application preferably carries out the crosslinking reaction at 80°C to ensure that soy protein isolate is fully expanded and participates in the construction of the crosslinking network.

[0037] In some embodiments of this implementation, after adding carboxymethyl cellulose, the temperature is adjusted to 45-55°C, specifically 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc., preferably 48-52°C, and most preferably 50°C. An alkaline condition of 80°C is necessary to promote the full thermal denaturation and expansion of soy protein isolate, exposing its internal active groups; however, prolonged stirring of carboxymethyl cellulose at this temperature easily leads to molecular chain degradation, and the rapid hydration of the carboxymethyl cellulose particles at high temperatures forms a gel shell, which is detrimental to its uniform dispersion. Therefore, this invention preferably involves lowering the temperature to 50°C after the soy protein isolate has fully denatured before adding carboxymethyl cellulose for blending and stirring. This ensures that the carboxymethyl cellulose is uniformly interspersed between the soy protein isolate chains and effectively protects the integrity of its molecular chains, thereby providing a uniform and stable precursor system for the subsequent double crosslinking of phytic acid. When the temperature is adjusted to 48-52°C, the membrane exhibits even better of the above-mentioned properties.

[0038] In some embodiments of this implementation, after adding carboxymethyl cellulose, the thermal reaction time is 100-300 min, specifically 100 min, 120 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 210 min, 220 min, 230 min, 240 min, 250 min, 260 min, 280 min, 300 min, etc., preferably 150-250 min, more preferably 180-200 min. In this invention, after adding carboxymethyl cellulose, the temperature is lowered to 48-52℃ (preferably 50℃) and stirring is continued for a long time (e.g., 180 min). This process parameter setting is based on the unique solubility characteristics of carboxymethyl cellulose. As a high-molecular-weight polysaccharide, the dissolution process of carboxymethyl cellulose includes two stages: surface hydration and internal permeation hydration. If the stirring time is too short, the carboxymethyl cellulose powder will only undergo surface hydration, leaving the interior undissolved. This results in a large number of poorly dispersed carboxymethyl cellulose gel particles in the film-forming solution, ultimately leading to uneven film structure and deterioration of mechanical and barrier properties. Conversely, if the stirring time is too long, prolonged mechanical shearing may cause degradation of the carboxymethyl cellulose molecular chains, leading to a decrease in viscosity. Stirring at 48–52°C for 180–200 minutes ensures that the carboxymethyl cellulose is fully hydrated and dissolved, and uniformly intercalates with the soy protein isolate molecular chains, forming a homogeneous and stable blend precursor system. This provides an ideal network basis for the subsequent phytic acid double crosslinking reaction.

[0039] In some embodiments of this implementation, the phytic acid content of the protein is 1-3 wt.%, specifically 1 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.5 wt.%, 2.8 wt.%, 3 wt.%, etc., preferably 1.5-2.5 wt.%. Experiments have shown that adding phytic acid can increase tensile strength, improve the membrane's thermal stability and brittleness, and enhance hydrophobic properties. When the phytic acid content of the protein is 1.9-2.1 wt.%, the membrane exhibits even better of the above-mentioned properties.

[0040] In some embodiments of this implementation, after adding phytic acid, the temperature is adjusted to 75-85°C, specifically 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, etc., preferably 78-82°C. If the temperature is too low, the globular protein structure of soy protein isolate does not fully unfold, and its internal cationic amino acid residues cannot be effectively exposed, resulting in phytic acid only partially crosslinking carboxymethyl cellulose and failing to form an effective electrostatic salt bridge with soy protein isolate, ultimately leading to an incomplete crosslinking network. If the temperature is too high, soy protein isolate undergoes excessive denaturation and irreversible aggregation, and the carboxymethyl cellulose molecular chains may also undergo slight degradation, leading to increased film brittleness. When the temperature is adjusted to 78-82°C, the membrane exhibits better of the above-mentioned properties.

[0041] Furthermore, after adding phytic acid, the thermal reaction time is 70-170 min, specifically 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, and 170 min, preferably 110-130 min. If the time is too short, the phytic acid has not fully diffused and established cross-links with the active sites of soy protein isolate and carboxymethyl cellulose; if the time is too long, the cross-linking has reached equilibrium, and further extending the reaction time does not further enhance the film performance. Instead, prolonged heating may lead to slight degradation of carboxymethyl cellulose or excessive Maillard reaction. When the time is adjusted to 110-130 min, the film exhibits better of the aforementioned properties.

[0042] Therefore, this invention ultimately determined 80℃ and 120min as the optimal process parameters for the phytic acid crosslinking reaction. These parameters ensure that phytic acid fully exerts its role as a double crosslinking bridge to form a dense and complete crosslinking network, thereby endowing the film with excellent mechanical properties, hydrophobicity, and thermal stability.

[0043] In some embodiments of this implementation, the drying temperature is 30~50℃, specifically 30℃, 35℃, 36℃, 37℃, 38℃, 39℃, 40℃, 41℃, 42℃, 43℃, 44℃, 45℃, 50℃, etc., preferably 35~45℃. Experiments have shown that the drying temperature also affects the film strength, with better film strength observed at this temperature. The film strength is even higher when the drying temperature is 39~41℃. The drying time is 6~10h, specifically 6h, 7h, 7.5h, 8h, 8.5h, 9h, 10h, etc., preferably 7.5~8.5h.

[0044] In some embodiments of this implementation, after drying, the membrane is placed in an environment with a relative humidity of 42-44% for equilibration. The equilibration time is 22-26 hours. The environment with a relative humidity of 42-44% is a desiccator containing a saturated aqueous solution of potassium carbonate.

[0045] In one embodiment, the present invention provides the application of a phytic acid double crosslinked protein / carboxymethyl cellulose composite film in packaging and / or as a substitute for conventional plastic products.

[0046] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0047] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.

[0048] Materials: Soy protein isolate (purity: dispersible) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Sodium carboxymethyl cellulose (degree of substitution 0.9, viscosity range 2500–4500 MPa·s) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. 70% phytic acid solution, gelatin (biotechnology grade), glycerol (99%), HCl (concentration: 0.1 mol / L), and NaOH (analytical grade) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0049] Performance testing methods: (1). Fourier transform infrared spectroscopy analysis FTIR spectra of the thin film samples were acquired using a Thermo Fisher-Nicole iS 5 micro-infrared spectrometer. The thin film sample size was 2 cm x 2 cm, and the scanning wavelength range was 4000–400 cm⁻¹. -1 The analysis was performed using attenuated total reflectance (ATR), with 64 scans per spectrum.

[0050] (2). X-ray diffraction analysis The compatibility properties of the thin film were determined by grazing incidence X-ray diffraction (Kα-smartlab 9kW, Japan) at an incident angle of 0.5°. The test conditions were 40 kV, copper radiation angle 2θ of 10°-40°, and scanning speed of 10° / min.

[0051] (3) Differential scanning thermal analysis Differential scanning calorimetry (DSC) was performed on a TA-Discovery 25 thermal analyzer. The sample size was 10 mg, and the system was protected against nitrogen (N2). The temperature scan range was 30 °C to 250 °C, and the heating rate was 5 °C / min.

[0052] (4) Thermogravimetric analysis The thermal stability of the composite membrane was analyzed using a thermogravimetric analyzer (NETZSCH, F3Tarsus®, Germany). Before the test, the weight of each sample was controlled to be approximately 3 mg. During the test, the composite membrane was tested at a heating rate of 10 °C / min, with a test temperature range of 40 °C–800 °C.

[0053] (5). Scanning electron microscopy analysis The surface and cross-sectional morphology of the composite film were characterized using a thermal field scanning electron microscope (Hitachi, SU-70, Japan). All composite film samples were sputter-coated with gold at a low current of 10 A for 2 minutes, and then the surface and cross-sectional morphology of the composite film samples were observed at a voltage of 10 kV.

[0054] (6). Water contact angle test The water contact angle is an important test method for characterizing the wettability of composite membrane surfaces. This experiment used a visual optical contact angle meter (DSA100S, KRüSS, Shanghai) to test and analyze the water contact angle of the composite membrane. During the test, a pre-prepared 2cm*2cm square composite membrane sample was attached to a glass slide, which was then placed under the meter. A drop of ultrapure water (2μL) was then placed on the surface of the composite membrane, and the change in contact angle was observed over 5 seconds. After the test, the image of the water contact angle of the composite membrane over 5 seconds was saved, and the numerical value of the water contact angle was recorded.

[0055] (7). Tensile property test The film thickness was measured using a thickness gauge with an accuracy of 0.001 mm (Lyca Electronic Equipment Co., Ltd., Dongguan, China). Five points were randomly selected, and the average value was calculated to ensure accuracy. To characterize the mechanical properties of the film, the tensile properties of the composite film were tested using a ZQ-990LA electric tensile testing machine (ZQ, Dongguan). Before the tensile test, the sample was made into a rectangular strip of 100 mm * 10 mm, and the tensile speed was set to 5 mm / min, according to ASTM D882.97 (ASTM, 2000b). The stress (σ)-strain (ε) curves during the tensile process were recorded, and the tensile strength and elongation at break were subsequently calculated based on these curves. The tensile properties of the film samples were the average values ​​of five repeated tests.

[0056] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0057] Example 1: Optimization of the solid-liquid ratio of soy protein isolate to deionized water (1) Add soy protein isolate to deionized water in a beaker at solid-liquid ratios of 1:10 g / ml, 1:20 g / ml, and 1:30 g / ml, respectively. Heat to 80°C and maintain for 30 min. Then adjust the pH to 10 and stir magnetically until completely dissolved.

[0058] (2) Remove the beaker and add glycerol of 40 wt.% of the soy protein isolate in 100 ml of deionized water. Continue to stir magnetically until fully mixed.

[0059] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0060] (4) After the reaction is complete, remove the beaker and cool it to room temperature. Then pour the film-forming solution into a square petri dish. Preheat the oven to 40°C and place the petri dish in the oven to dry for 8 hours.

[0061] (5) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0062] The solid-liquid ratio of soy protein isolate to deionized water was optimized for the preparation of composite films using tensile strength and elongation at break as indicators. The results are shown in Table 1. When the solid-liquid ratio of soy protein isolate to deionized water was 1:20 g / ml, the tensile strength of the film reached a maximum of 6.31±0.75 MPa and the elongation at break was 20.53±10.79%.

[0063] Based on the above reasons, it can be concluded that the tensile properties of the film are optimal when the solid-liquid ratio of soy protein isolate to deionized water is 1:20 g / ml. Therefore, a solid-liquid ratio of 1:20 g / ml of soy protein isolate to deionized water is selected as the optimal concentration for subsequent optimization of the preparation process.

[0064] Table 1. Effect of different solid-liquid ratios of soy protein isolate and deionized water on the tensile properties of films.

[0065] Example 2: Optimization of Glycerol Mass Fraction (1) Add soy protein isolate and deionized water to a deionized water beaker at a solid-liquid ratio of 1:20 g / ml, heat to 80℃ and maintain for 30 min, then adjust the pH to 10 and stir magnetically until completely dissolved.

[0066] (2) Remove the beaker and add glycerol at a weight of 30 wt.%, 40 wt.%, and 50 wt.% of the soy protein isolate, respectively, and continue to stir magnetically until fully mixed.

[0067] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0068] (4) After the reaction is complete, remove the beaker and cool it to room temperature. Then pour the film-forming solution into a square petri dish. Preheat the drying oven to 40°C and place the petri dish in the drying oven to dry for 8 hours.

[0069] (5) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0070] The mass fraction of glycerol added for composite membrane preparation was optimized using tensile strength and elongation at break as indicators. The results are shown in Table 2. As the mass fraction of glycerol in zein increased, the tensile strength of the composite membrane gradually decreased, but the elongation at break gradually increased. When the mass fraction of glycerol in soy protein isolate was 40 wt.%, the tensile strength of the film was slightly lower than that at 30 wt.%, but the elongation at break was much higher than that at 30 wt.%. Although the elongation at break was highest at 50 wt.%, the tensile strength was still lower than that at 30 wt.% and 40 wt.%. Therefore, using tensile performance as an indicator, a glycerol mass fraction of 40 wt.% was selected as the optimal mass fraction for subsequent optimization of the composite membrane preparation process.

[0071] Table 2. Effect of different mass fractions of glycerol on the tensile properties of the film.

[0072] Example 3: Optimization of gelatin mass fraction (1) Add soy protein isolate and deionized water to a deionized water beaker at a solid-liquid ratio of 1:20 g / ml, heat to 80℃ and maintain for 30 min, then adjust the pH to 10 and stir magnetically until completely dissolved.

[0073] (2) Remove the beakers and add 40 wt.% glycerol, which accounts for 10 wt.% , 20 wt.% , and 30 wt.% glycerol, respectively, which account for 10 wt.% , 20 wt.% , and 30 wt.% glycerol, respectively. Continue to stir magnetically until fully mixed.

[0074] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0075] (4) After the reaction is complete, remove the beaker and cool it to room temperature. Then pour the film-forming solution into a square petri dish. Preheat the drying oven to 40°C and place the petri dish in the drying oven to dry for 8 hours.

[0076] (5) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0077] The mass fraction of gelatin added for the preparation of the composite film was optimized using tensile strength and elongation at break as indicators. The results are shown in Table 3. When the mass fraction of gelatin in soy protein isolate was 20 wt.%, the tensile strength of the film was significantly higher than that at mass fractions of 10 wt.% and 30 wt.%, and the elongation at break was also optimal. Therefore, using tensile performance as an indicator, a mass fraction of 20 wt.% of gelatin was selected as the optimal mass fraction for subsequent optimization of the composite film preparation process.

[0078] Table 3. Effect of different mass fractions of gelatin on the tensile properties of films.

[0079] Example 4: Optimization of drying temperature (1) Add soy protein isolate and deionized water to a deionized water beaker at a solid-liquid ratio of 1:20 g / ml, heat to 80℃ and maintain for 30 min, then adjust the pH to 10 and stir magnetically until completely dissolved.

[0080] (2) Remove the beakers and add 40 wt.% glycerol to each beaker, and 20 wt.% gelatin to each beaker. Continue to stir magnetically until fully mixed.

[0081] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0082] (4) After the reaction is complete, remove the beaker and cool it to room temperature. Then pour the film-forming solution into a square petri dish. Dry the film in a drying oven at 30℃, 40℃, and 50℃ for 8 hours respectively.

[0083] (5) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0084] The drying temperature for the composite film was optimized using tensile strength and elongation at break as indicators. The results are shown in Table 4. As the drying temperature increased, the tensile strength of the film first increased and then decreased. The tensile properties of the composite film reached the optimal value when the drying temperature was 40℃, with a tensile strength of 11.88±1.26 MPa and an elongation at break of 18.85±5.42%. Therefore, based on the tensile properties, the subsequent drying temperature of the composite film was selected at 40℃.

[0085] Table 4. Effect of different drying temperatures on the tensile properties of the film.

[0086] Example 5: Optimization of phytic acid mass fraction ((1) Add soy protein isolate and deionized water to a deionized water beaker at a solid-liquid ratio of 1:20 g / ml, heat to 80℃ and maintain for 30 min, then adjust the pH to 10 and stir magnetically until completely dissolved.

[0087] (2) Remove the beakers and add 40 wt.% glycerol to each beaker, and 20 wt.% gelatin to each beaker. Continue to stir magnetically until fully mixed.

[0088] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0089] (4) Remove the beaker and add carboxymethyl cellulose at a mass fraction of 10 wt.% of soybean protein isolate. Continue to stir magnetically at 50°C for 180 min until fully mixed.

[0090] (5) Remove the beaker, adjust the pH to 7, and add phytic acid at a weight percentage of 1 wt.%, 2 wt.%, and 3 wt.% of the soybean protein isolate, respectively. Heat to 80°C and continue to stir magnetically for 120 minutes until fully mixed.

[0091] (6) After the reaction is complete, remove the beaker, cool it to room temperature, and then pour the film-forming solution into a square petri dish. Dry the mixture in a drying oven at 40°C for 8 hours.

[0092] (7) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0093] The amount of phytic acid added was optimized for preparing phytic acid-crosslinked soybean protein isolate / carboxymethyl cellulose composite membranes, using tensile strength and elongation at break as indicators. The results are shown in Table 5. With increasing phytic acid content, the elongation at break of the film first increased and then decreased, while the tensile strength showed little difference. When the phytic acid content accounted for 2 wt.% of the soybean protein isolate mass fraction, the tensile properties of the composite membrane reached their optimal level, with a tensile strength of 13.22 ± 0.55 MPa and an elongation at break of 36.82 ± 6.18%. Therefore, based on tensile properties, the composite membrane was dried at 40℃.

[0094] Table 5. Effect of different mass fractions of phytic acid on the tensile properties of the film.

[0095] Example 6: Optimization of Carboxymethyl Cellulose Mass Fraction (1) Add soy protein isolate and deionized water to a deionized water beaker at a solid-liquid ratio of 1:20 g / ml, heat to 80℃ and maintain for 30 min, then adjust the pH to 10 and stir magnetically until completely dissolved.

[0096] (2) Remove the beakers and add 40 wt.% glycerol to each beaker, and 20 wt.% gelatin to each beaker. Continue to stir magnetically until fully mixed.

[0097] (3) The fully mixed dispersion was stirred in a magnetic stirrer at 80°C for 30 minutes.

[0098] (4) Remove the beaker and add carboxymethyl cellulose at a weight percentage of 4 wt.%, 10 wt.%, and 16 wt.% of soybean protein isolate, respectively. Continue to stir magnetically at 50°C for 180 min until fully mixed.

[0099] (5) Remove the beaker, adjust the pH to 7, add phytic acid at a weight of 2 wt.% of the soybean protein isolate, heat to 80°C and continue magnetic stirring for 120 min until fully mixed.

[0100] (6) After the reaction is complete, remove the beaker, cool it to room temperature, and then pour the film-forming solution into a square petri dish. Dry the mixture in a drying oven at 40°C for 8 hours.

[0101] (7) After drying, the film is cooled to room temperature, gently peeled off with tweezers, and placed in a desiccator (containing a saturated potassium carbonate aqueous solution) with a relative humidity of 43% for 24 hours to equilibrate.

[0102] The membrane prepared by omitting steps (4) and (5) is designated as a; the membrane prepared by omitting step (5) and having a carboxymethyl cellulose content of 10 wt.% of soybean protein isolate is designated as b; the membrane prepared by having a carboxymethyl cellulose content of 4 wt.% of soybean protein isolate is designated as c; the membrane prepared by having a carboxymethyl cellulose content of 10 wt.% of soybean protein isolate is designated as d; and the membrane prepared by having a carboxymethyl cellulose content of 16 wt.% of soybean protein isolate is designated as e.

[0103] Performance Analysis: (1) Infrared spectroscopy analysis Infrared spectra of soy protein isolate films with different compositions are shown below. Figure 1 As shown in the figure. The infrared spectrum shows a typical stretching vibration peak at -OH, with a wavelength of 3000 cm⁻¹. -1-3500 cm -1 This is mainly due to the free stretching vibrations of -OH groups both within and between molecules. (2550-3000 cm⁻¹) -1 The peaks between these values ​​represent the CH stretching vibration peaks of aliphatic alkyl groups. The shoulder peak is at 1530 cm⁻¹. -1 The nearby absorption peaks are typically a combination of the bending vibration of NH and the stretching vibration of CN. These bands correspond to the spectrum of soybean protein and are also related to the peptide bond structure in the protein, further confirming the presence of peptide bonds. The shapes of these peaks all exhibit the typical structure of protein molecules. In films with added phytic acid, the peak value is 1630.1 cm⁻¹. -1 and 1542.5cm -1 The nearby absorption peaks are typically associated with the amide I and amide II bands of proteins, reflecting secondary structure information. This indicates that the structure of the soy protein isolate was present in the mixed membrane during the experiment, and the phytic acid-mediated double cross-linking did not affect the protein's secondary structure or alter the peptide bond vibrational characteristics. (1239.5 cm⁻¹) -1 -1396.8cm -1 The absorption bands correspond to CN stretching vibrations. These phenomena demonstrate that a Maillard reaction occurred between soy protein isolate and carboxymethyl cellulose in the film without phytic acid. During the phytic acid double crosslinking process, the -OH groups in carboxymethyl cellulose and the amino groups in soy protein isolate were consumed during film preparation. In the film without phytic acid, the absorption band at 1064.2 cm⁻¹... -1 The peak at this point is attributed to vibrations, such as out-of-plane CH bending from aromatic structures. However, in the duplex, the peak position is shifted to some extent due to the POC stretching band of the phytic acid molecule. In films with added phytic acid, the peak intensity here increases due to the presence of P=O bonds in phytic acid. And the peak position is shifted to some extent due to the POC stretching band of the phytic acid molecule. 922 cm⁻¹ -1 The peak value is related to the bending and stretching vibrations of phytic acid molecules (PO), but it may also be related to the bending vibrations of CH. 848.8 cm⁻¹ -1 The peak at 1623 cm⁻¹ may be related to C–C stretching vibrations. -1 -1630cm -1 The peak value indicates the presence of bound water, thus forming hydrogen bonds. The enhancement of the peak signal of the phytic acid double crosslinking group is also related to the P-OH vibration in the phytic acid molecule.

[0104] Different contents of carboxymethyl cellulose may lead to differences in the chemical structure and composition of the mixed membrane, resulting in different absorption characteristics in the infrared spectrum. As can be seen from the figure, at 3277 cm⁻¹... -1The absorption peaks in the vicinity show slight variations in intensity with increasing carboxymethyl cellulose content. This is because changes in carboxymethyl cellulose content affect the formation and distribution of hydrogen bonds in the mixed membrane. Hydrogen bonds can form between the phosphate groups of phytic acid and the hydroxyl groups on the sodium carboxymethyl cellulose molecular chain, and the phosphate groups of phytic acid can also form hydrogen bonds with the amino groups in soybean protein.

[0105] (2) X-ray diffraction test and analysis The crystal structure of the composite thin film was analyzed by X-ray diffraction, such as... Figure 2 As shown, the marker formed by cross-linking soy protein isolate with phytic acid still retains the crystal structure of soy protein isolate. Soy protein isolate exhibits strong characteristic reflections at approximately 2θ = 20°. With the addition of carboxymethyl cellulose (CMC) to the film, the CMC / soy protein isolate mixture still shows strong reflections at the peak, but the reflection intensity is significantly reduced compared to pure soy protein isolate. Therefore, the crystal structure of soy protein isolate is gradually disrupted through mixing with CMC. The peaks of the film are enhanced by the double cross-linking with phytic acid, indicating that the addition of phytic acid helps maintain the crystal structure of soy protein isolate and suggests an increase in hydrogen bonds in the film. This indicates that more carboxyl groups participate in phytic acid-mediated hydrogen bond-coordination cross-linking, a phenomenon that makes the film structure compact and uniform, improving the film's transparency, mechanical properties, and hydrophobicity. Compared to the soy protein isolate film, the diffraction peaks of the phytic acid-mediated double cross-linked film are broader and less intense, indicating that the double cross-linking network introduces more amorphous structures while maintaining the overall integrity of the film. Notably, no new crystallization peaks appear in the spectrum, confirming that the components are uniformly mixed and no phase separation occurs.

[0106] (3) Differential thermal analysis Determining Tg is another effective method for assessing thin film compatibility. Figure 3 As can be seen, soy protein isolate exhibits an endothermic peak around 120℃, which is its Tg value. The carboxymethyl cellulose / soy protein isolate samples all possess a unique Tg value between 110-120℃. The individual Tg values ​​of the mixed polymers in the differential thermal analysis scan indicate good polymer compatibility. Phytic acid double crosslinking forms strong chelate bonds with the amino groups of soy protein isolate and the hydroxyl groups of carboxymethyl cellulose. These bond energies are higher than ordinary hydrogen bonds. This "strong crosslinking" significantly enhances the binding force of the molecular chains and restricts their mobility, resulting in a higher Tg value than the pure soy protein isolate / carboxymethyl cellulose mixed membrane.

[0107] The figure also shows a shoulder peak. The small peak after the addition of carboxymethyl cellulose originates from the physical cross-linking network formed by dense hydrogen bonds between carboxymethyl cellulose and soy protein isolate, which binds glycerol and bound water and delays volatilization. After the introduction of phytic acid, phosphate groups form ionic bonds with protein amino groups, constructing a second chemical cross-linking domain within the physical network. The small peak shifts towards higher temperatures and becomes sharper with increasing cross-linking density, indicating a progressive evolution from physical blending to a double cross-linking network, which corroborates the good compatibility of the components.

[0108] (4) Thermogravimetric analysis The thermal stability of the thin film was characterized using thermogravimetric analysis, such as... Figure 4 As shown. Overall, all films exhibited four stages of weight loss, but the range of these stages varied between groups. Soy protein isolate decomposed at a relatively low temperature (approximately 100°C), with an initial weight loss of about 5% due to moisture loss below 100°C. Carboxymethyl cellulose typically decomposed in a two-stage process. The initial weight loss was attributed to the presence of a small amount of moisture, while the second weight loss came from CO2 in the COO-group of carboxymethyl cellulose. For the three groups of films with added phytic acid: the first stage occurred in the temperature range of 57.9°C to 131.9°C, resulting in a weight loss of approximately 12%. This weight loss was primarily due to the volatilization of free water and a small amount of volatile small molecules in the active film. The second stage occurred in the temperature range of 191.6°C to 237.5°C. The main reason for the weight loss in this stage was the evaporation of low molecular weight compounds, including the plasticizer compound glycerol and its chemisorbed water molecules, as well as structural changes in bound water in the low molecular weight protein components or membrane network. In this stage, the thermal degradation temperature of the active membrane with added phytic acid was higher than that of the blank membrane, indicating that phytic acid can improve membrane stability through double crosslinking of soy protein isolate and carboxymethyl cellulose. The third stage occurred between 234.5 ℃ and 347.7 ℃, with the active membrane losing approximately 20%–60% of its weight. The main reason for the quality degradation in this stage was the destruction of proteins and other macromolecules. The fourth stage occurred between 380.2 ℃ and 543.5 ℃, and the weight loss in this stage was likely caused by polymer carbonization. In the phytic acid-mediated double crosslinked soy protein isolate and carboxymethyl cellulose mixed membrane, although the double crosslinking effect of phytic acid enhanced intermolecular interactions, and although phytic acid itself decomposes and volatilizes at intermediate temperatures, the overall weight loss rate was slightly slowed. The hydroxyl groups of the carboxymethyl cellulose molecular chain can form stronger hydrogen bonds with soy protein isolate / phytic acid, improving the thermal stability of the mixed membrane. As the content of carboxymethyl cellulose in the blend increased, the decomposition rate of the sample decreased. Phytic acid can form hydrogen bonds with the amino groups of soy protein isolate and the hydroxyl groups of carboxymethyl cellulose, which enhances the degree of cross-linking between molecules, improves the thermal stability of the mixed membrane, and slows down the degradation of polymer chains.

[0109] (5) Surface and cross-sectional morphology analysis The microstructure characteristics of the active thin film were effectively visualized using scanning electron microscopy. Figure 5 The morphological characteristics of the surface and cross-section of soy protein isolate films with different components are shown. As shown in the figure, the pure soy protein isolate film has a relatively smooth microstructure, with a flat and uniform surface and cross-section, indicating that soy protein isolate has good film-forming ability. This suggests that soy protein isolate, glycerol, and gelatin are uniformly mixed. Soy protein isolate and carboxymethyl cellulose form a cross-linked structure through the Maillard reaction. The figure shows good compatibility between the two components, with the soy protein isolate and carboxymethyl cellulose fully mixed in the composite film, forming a single continuous phase. The film exhibits a distinct yellow hue, derived from the inherent color of soy protein isolate. All films with added phytic acid have a relatively flat and uniform surface, enhancing the original color of the film, making it lighter and more transparent. This observation indicates that phytic acid has strong cross-linking properties and can improve the compatibility between label components. The cross-section of the film with added phytic acid shows a fine wrinkled and interwoven network structure, maintaining overall continuity, but the texture is more pronounced than the film without added phytic acid. The double cross-linking effect of phytic acid forms strong chelate bonds with the amino groups of soy protein isolate and the hydroxyl groups of carboxymethyl cellulose, forming a tighter entangled structure. Tiny bumps and depressions are visible in some areas, indicating an increase in membrane roughness after the introduction of phytic acid, but no obvious pores or cracks appear, and the film-forming properties remain good. With increasing carboxymethyl cellulose content, the network structure on the membrane surface becomes denser, the distribution of wrinkles is more uniform, and the amplitude of bumps and depressions decreases. Higher concentrations of carboxymethyl cellulose enhance the double cross-linking effect of phytic acid, forming a more synergistic cross-linking system and a more regular microstructure on the membrane surface. This change typically helps improve the mechanical strength and water resistance of the membrane. This structure indicates that the component compatibility of the membrane improves with increasing carboxymethyl cellulose content, which helps optimize the membrane's flexibility and stability.

[0110] In summary, the surface of pure soy protein isolate film is relatively smooth and uniform, without obvious cracks, and its cross-section exhibits a relatively dense structure. After adding carboxymethyl cellulose, slight irregularities and small granular protrusions appear on the film surface. The cross-section remains continuous, but its texture is slightly increased compared to pure soy protein isolate film. After introducing phytic acid for double cross-linking, the film surface becomes even smoother and denser, with locally visible fine protrusions and depressions. The cross-section exhibits a distinct fine wrinkle and interwoven network structure, while maintaining overall continuity. As the carboxymethyl cellulose content increases, the network structure on the film surface becomes denser, the wrinkle distribution becomes more uniform, and the amplitude of protrusions and depressions decreases. The cross-section shows a more regular and compact interwoven network. When the carboxymethyl cellulose content further increases to 0.8g, although the surface still maintains a certain degree of regularity, some discontinuities and more obvious granular aggregations begin to appear in the cross-section.

[0111] (6) Analysis of surface hydrophobic properties The contact angle of a water droplet on the film surface (angle after 5 seconds) indicates the hydrophobicity of the film. Figure 6 Generally, surfaces with a contact angle greater than 90° are considered hydrophobic, while those less than 90° are considered hydrophilic. Pure soy protein isolate films have a water contact angle of approximately 50°, exhibiting overall hydrophilicity. This is likely due to the high content of polar amino acids in soy protein isolate, which contributes to its high hydrophilicity. Adding glycerol and gelatin increases the water contact angle to 70.59°. The addition of gelatin and glycerol as plasticizers reduces water molecule penetration by forming a dense network structure, thus improving the membrane's hydrophobic properties. Adding carboxymethyl cellulose increases the water contact angle to 75.77°. This is because the carboxyl groups on the carboxymethyl cellulose molecular chain can associate with the amino and carboxyl groups of soy protein isolate through hydrogen bonds and electrostatic attraction, forming an intermolecular cross-linked network. This network encapsulates some of the free hydrophilic groups within the membrane, reducing the hydrophilic sites on the membrane surface and thus decreasing water molecule adsorption, thereby increasing the water contact angle.

[0112] Notably, after adding phytic acid for crosslinking, the water contact angle of the composite film exceeded 90°, indicating that the film exhibited slight hydrophobicity rather than the previous hydrophilicity. The water contact angle also increased with increasing carboxymethyl cellulose content, with 0.2g, 0.5g, and 0.8g carboxymethyl cellulose showing angles of 105.54°, 107.03°, and 108.3°, respectively. The introduction of phytic acid was the key driver of the significant increase in the water contact angle, its core role stemming from its chelating crosslinking properties and regulation of hydrophilic groups. Phytic acid molecules contain multiple phosphate groups, which can form stable coordination chelates with the amino groups on the soy protein isolate molecular chains, and simultaneously construct a multiple hydrogen bond-coordination crosslinking network with the carboxyl groups of carboxymethyl cellulose. This strong interaction promotes the tight entanglement of the system's molecular chains, encapsulating a large number of free hydrophilic groups (amino and carboxyl groups) inside the membrane, significantly reducing the number of hydrophilic sites on the membrane surface and lowering the surface's adsorption capacity for water molecules. When the carboxymethyl cellulose content is 0.2g, a basic cross-linked network has been formed in the system. The carboxyl groups of carboxymethyl cellulose are moderately entangled with the polar groups of phytic acid and soy protein isolate, which reduces the number of free hydrophilic groups on the surface and maintains the continuity of the membrane structure under the phytic acid-mediated double cross-linking effect. At this time, the membrane surface roughness is moderate, and combined with the "cushion" effect of the Cassie-Baxter model, the contact angle reaches a high level. In this process, the phytic acid-mediated double cross-linking effect is the key to improving hydrophobicity. Multiple phosphate groups of phytic acid molecules form stable coordination bonds with the amino groups of soy protein isolate, and at the same time, they form a hydrogen bond-coordination cross-linking network with the carboxyl groups of carboxymethyl cellulose, which encapsulates a large number of hydrophilic groups inside the membrane, significantly reducing the surface adsorption capacity for water molecules. As the carboxymethyl cellulose content increases, more carboxyl groups participate in the cross-linking reaction, forming a denser and more uniform network structure with phytic acid and soy protein isolate components, further encapsulating hydrophilic groups. Simultaneously, the membrane surface texture becomes more regular, allowing for more complete exposure of hydrophobic amino acid residues (alanine, valine, etc.) in the soy protein isolate, reducing membrane surface energy to a lower level and synergistically promoting an increase in contact angle. The cross-linking effect of phytic acid is further enhanced at this stage; its mediated rigid network prevents excessive molecular chain movement that could expose hydrophilic groups, thus reinforcing the hydrophobic "cushion" effect.

[0113] In short, at specific carboxymethyl cellulose loadings, phytic acid-assisted double crosslinking technology can transform hydrophilic soy protein isolate into a film with excellent hydrophobic properties, highlighting the crucial role of network integrity in determining hydrophobicity.

[0114] (7) Mechanical performance analysis Figure 7The tensile strength and elongation at break of soy protein isolate-based composite films under different compositional conditions were demonstrated. Among the testable samples, the phytic acid-free soy protein isolate-carboxymethyl cellulose (CMC) hybrid film exhibited a tensile strength of 12.12 MPa and an elongation at break of 14.25%. After introducing phytic acid and combining it with a small amount of CMC, the tensile strength slightly increased to 12.54 MPa, while the elongation at break significantly improved to 35.67%. With further increases in CMC content, the elongation at break reached a maximum of 39.93%, while the tensile strength also slightly increased to 13.22 MPa. These results indicate that phytic acid-mediated double crosslinking effectively enhances the mechanical properties of the soy protein isolate / CMC network, significantly improving its ductility. When the CMC content was further increased to 0.8 g, the tensile strength slightly increased to 15.63 MPa, but the elongation at break decreased sharply to 4.395%. This finding suggests that there is an optimal CMC concentration during network formation. Excessive carboxymethyl cellulose may disrupt the continuity of the cross-linked network, resulting in a loss of elongation at break.

[0115] The reasons for the above phenomena can be summarized as follows: The significant increase in extensibility at low carboxymethyl cellulose concentrations is due to the fact that in the phytic acid-mediated double crosslinking, multiple phosphate groups of phytic acid molecules form electrostatic salt bonds with the amino groups of soy protein isolate, while simultaneously constructing a hydrogen bond-coordination crosslinking network with the carboxyl groups of carboxymethyl cellulose. This reduces network defects and significantly increases the elongation at break. Oversaturation of crosslinking density occurs when high concentrations of carboxymethyl cellulose competitively consume phosphate groups of phytic acid, reducing effective crosslinking sites and severely restricting protein chain activity. This causes the film to lose its plastic deformation ability, resulting in a hard and brittle film. Excessive introduction of hydrophilic sites is also a factor. Carboxymethyl cellulose is rich in hydrophilic groups, and excessive amounts lead to increased water adsorption. This disrupts the uniformity of water molecules acting as plasticizers in the film, resulting in both localized over-plasticization and localized cracking, ultimately worsening the extensibility.

[0116] These findings demonstrate that, at the optimal carboxymethyl cellulose loading, phytic acid-assisted double crosslinking can transform brittle soy protein isolate into films with good mechanical properties, highlighting the crucial role of network integrity in determining mechanical properties.

[0117] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A phytic acid-crosslinked protein / carboxymethyl cellulose composite membrane, characterized in that, Its raw materials include phytic acid, protein, and carboxymethyl cellulose; Proteins and carboxymethyl cellulose form physical cross-linking points through strong intermolecular hydrogen bonds; negatively charged phytic acid forms electrostatic salt bonds with cationic groups in proteins; and the phosphate groups of phytic acid and carboxyl groups on the carboxymethyl cellulose molecular chain construct a multiple hydrogen bond-coordination cross-linking network.

2. The phytic acid double-crosslinked protein / carboxymethyl cellulose composite membrane according to claim 1, characterized in that, The protein includes soy protein isolate.

3. A method for preparing a phytic acid-crosslinked protein / carboxymethyl cellulose composite membrane according to claim 1 or 2, characterized in that, Includes the following steps: Dissolve the protein in water, heat and adjust the pH to alkaline, add glycerol and gelatin and continue heating to react, adjust the temperature and then add carboxymethyl cellulose and mix well. Then adjust the pH to neutral, add phytic acid to obtain the film-forming solution, and dry the film-forming solution to obtain the final product.

4. The preparation method according to claim 3, characterized in that, Adjust the pH to 8-10, preferably 9-10; Preferably, the solid-liquid ratio of protein to water is 1:10~30 g / mL, more preferably 1:15~25 g / mL; Preferably, the glycerol content is 30-50 wt.% of the protein mass, more preferably 35-45 wt.%. Preferably, the gelatin has a protein content of 10-30 wt.%, more preferably 15-25 wt.%. Preferably, the carboxymethyl cellulose has a protein mass fraction of 4-16 wt.%, more preferably 8-12 wt.%. Preferably, the phytic acid content of the protein is 1-3 wt.%, more preferably 1.5-2.5 wt.%.

5. The preparation method according to claim 3, characterized in that, The drying temperature is 30~50℃, preferably 35~45℃; Preferably, the drying time is 6 to 10 hours, and more preferably 7.5 to 8.5 hours.

6. The preparation method according to claim 3, characterized in that, The temperature for the heating reaction of protein and water is 70~90℃, preferably 75~85℃; Preferably, the reaction time of protein and water is 20-40 minutes.

7. The preparation method according to claim 3, characterized in that, After adding carboxymethyl cellulose, the temperature is adjusted to 40~60℃, preferably 45~55℃; Preferably, after adding carboxymethyl cellulose, the thermal reaction time is 100-300 min, more preferably 150-250 min, and even more preferably 180-200 min; Preferably, after adding phytic acid, the temperature is adjusted to 75~85℃, more preferably 78~82℃; Preferably, the thermal reaction time after adding phytic acid is 70-170 min, and more preferably 110-130 min.

8. The preparation method according to claim 3, characterized in that, After drying, the membrane is placed in an environment with a relative humidity of 40-45% for equilibration; the equilibration time is 20-30 hours.

9. The application of a phytic acid double crosslinked protein / carboxymethyl cellulose composite film according to claim 1 or 2, or a phytic acid double crosslinked protein / carboxymethyl cellulose composite film prepared by the preparation method according to any one of claims 3 to 8, in the packaging field.

10. A packaging material, characterized in that, The phytic acid double cross-linked protein / carboxymethyl cellulose composite membrane according to claim 1 or 2, or the phytic acid double cross-linked protein / carboxymethyl cellulose composite membrane prepared by the preparation method according to any one of claims 3 to 8.